Radical Molecular Modulator for High-Performance Perovskite Solar Cells - Peng, Qi; Zheng, Xin; Zhang, Xiaoru; You, Shuai; Li, Lin; Zhao, Yang; Zhang, Shujing; Luo, Long; Zeng, Haipeng; Li, Xiong (Frontiers in Chemistry, 2020)
The long-term stability of perovskite solar cells (PSCs) remains an issue impeding their commercialization. Generally, polycrystalline perovskite thin films have many defects on the grain boundaries, which affect the optoelectronic performance and stability of the devices under moisture, heat, illumination, and the presence of an electric field condition. The O-donor Lewis base is often employed to regulate the performance of PSCs such as carbonyl and carboxyl compounds. Herein, we have developed a concept of radical molecular modulation using the O-donor group for high-performance perovskite photovoltaic devices. The judiciously designed radical modulators 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), which located at the perovskite grain boundary through interaction with the perovskite surface sites, effectively passivated the surface defects while templating the formation of large grain crystal and high-quality perovskite thin films. Accordingly, the optimized TEMPO-modulated PSCs achieved a power conversion efficiency of 20.73% with superior stability. This work makes an important contribution for exploring the effect of radical in perovskites to improve the performance of PSCs and other optoelectronic devices.